Başarıda anahtar kelime: öz-yeterlik - (:unkn) unknown (My University, 2013)
Öz-yeterlik kavramı kırk yılı aşkın bir süredir dünya çapında yapılan pek çok bilimsel araştırmada öğrenci başarısında en etkili faktörlerin başında gösterilmektedir. Ülkemizde öz-yeterlik üzerine yapılan çalışmalarda son yıllarda artış görülmekle beraber araştırmalar çoğunlukla yükseköğretim düzeyini kapsamaktadır. Öz-yeterlik kavramına ilişkin alanyazın, öğrenme ortamlarında öz- yeterlik algısının geliştirilmesine yönelik çalışmalar, yönlendirme ve öneriler oldukça sınırlıdır. Bu çalışmanın amacı alanyazın taraması yönteminden faydalanarak, öz-yeterlik kavramına ilişkin bilimsel bir altyapı oluşturmak ve eğitim ortamlarında öğrencilerin öz-yeterlik algılarının geliştirilmesine yönelik önerilerde bulunmaktır. Araştırmada öz-yeterlik kavramının gelişimi ve önemi, ilişkili faktörler, öz-yeterlik kaynakları ve öğrenme ortamlarında akademik öz-yeterlik üzerine kuramsal ve deneysel çalışmalar paylaşılmıştır. Ayrıca, yapılan araştırmalardan yola çıkılarak eğitim ortamlarında öğrencilerin akademik öz- yeterliklerinin geliştirilmesine yönelik önerilerde bulunulmuştur.

A great deal of scientific research conducted around the world for more than 40 years has shown that the concept of self-efficacy is one of the most powerful factors influencing students’ academic performance. In Turkey, research related to self-efficacy has been increased in recent years but the studies conducted on this concept have primarily involved higher education level. The literature regarding self-efficacy as well as research, guidance and suggestions for improving students’ self-efficacy in learning environments are rather limited. The purpose of the current study was to construct a scientific background related to the concept of self-efficacy and to provide suggestions for improving students’ self-efficacy in learning environments. Literature review method was used for this investigation. The sections cover the development and the importance of self-efficacy concept, the factors associated with self-efficacy, the sources of self-efficacy and the theoretical and the empirical research on academic self-efficacy in learning environments. Further, based on the related research, suggestions were provided for improving students’ academic self-efficacy beliefs in educational environments.
Key word in success: self-efficacy
Keywords: Eğitim, Eğitim Araştırmaları